Coevolutionary Planning Processes - Gerrits, Lasse; Teisman, Geert (Complexity and Planning, 2012)
The chapter introduces complexity theory and outlines its relevance for spatial planning and governance. It examines a chronological history of events is provided in some detail based on the three key phases of Victorian State Government's metropolitan planning efforts for Melbourne between 1998-2005. Complexity theory was by no means the dominant framing for Melbourne's metropolitan planning but one of many influences. Complexity theory methodologies such as cellular automata modelling and use of genetic algorithms offer the potential to create simulations of aspects of urban systems that can reveal new insights into the dynamics of urban change. The process of developing an agent-based model using tools associated with complexity theory began in very small ways to stimulate new imagination and new insights about the nature of the dynamics of structural urban change in Melbourne. The chapter provides insight into how deliberate exploration of a complexity theory framework by planning practitioners influenced the metropolitan spatial planning process in Melbourne.